2001
DOI: 10.1093/treephys/21.8.513
|View full text |Cite
|
Sign up to set email alerts
|

Remobilization and uptake of N by newly planted apple (Malus domestica) trees in response to irrigation method and timing of N application

Abstract: Environmentally sound management of N in apple orchards requires that N supply meets demand. In 1997, newly planted apple trees (Malus domestica Borkh. var. Golden Delicious on M.9 rootstock) received daily applications of N for six weeks as Ca(15NO3)(2) through a drip irrigation system at a concentration of 112 mg l(-1) at 2-8, 5-11 or 8-14 weeks after planting. Irrigation water was applied either to meet estimated evaporative demand or at a fixed rate. In 1997, trees were harvested at 5, 8, 11 and 14 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
6
35
1
1
Order By: Relevance
“…The practices increasing cell number in fruit may promote firmness. During the cell division period, the most notably determining factor is the N content of trees accumulated in the previous year (Millard, 1996;Neilsen et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The practices increasing cell number in fruit may promote firmness. During the cell division period, the most notably determining factor is the N content of trees accumulated in the previous year (Millard, 1996;Neilsen et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the uptake of nitrogen is correlated with the rate of spring new growth. Reports on apple, peach, and mature almonds have also shown that uptake can be affected by high demands for N during the period of vigorous spring vegetative growth (Weinbaum et al, 1984b(Weinbaum et al, , 1987Munoz et al, 1993;Neilsen et al, 2001b).…”
Section: Uptake and Translocation Ofmentioning
confidence: 99%
“…For example, in apple trees, a combination of soil temperature and plant developmental stage influences the uptake and use of soil nitrogen in the spring . The timing of demand for root-supplied N may depend on whether flowering occurs (Neilsen et al, 2001b). In mature almond trees, the need for nitrogen that is triggered by the presence of fruits may also be involved in regulating its uptake (Weinbaum et al, 1984b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption of urea through dormant woody tissues was found to be considerable (Tukey and Ticknor 1952). Nitrogen reserves are responsible for supporting early season growth and flowering through remobilization (Millard 1996;Millard and Neilsen 1989;Neilsen et al 2001). Recently, labelled urea 15 N has been used to quantify leaf absorption more precisely and to measure directly the increase in N reserves attributable to urea sprays (Rosecrance et al 1998;Tagliavini et al 1998;Sanchez et al 1990).…”
mentioning
confidence: 99%